EFFECTIVENESS OF TIME IRRADIATION BY LASER DIODE 650 NM AND PHOTOSENSITIZER Methylene Blue ON DECREASING THE NUMBER OF MIXED BACTERIAL COLONIES FROM NECROTIC ROOT CANAL - Nadya Ayusandra Larasati; Kun Ismiyatin; Sri Kunarti (Conservative Dentistry Journal, 2019)
Background. Pulp necrosis is defined as the irreversible death of pulp tissue. It clinically observed by the destruction of its own tissue. The primary etiology of pulp necrosis is irritation due to bacterial infection. The treatment for pulp necrosis is root canal treatment with a success percentage ranging from 40-93% based on cavities with minimal bacteria that can be sterilized. One method of sterilization using Antibacterial Photodynamic Therapy (aPDT), which uses laser diodes is currently being developed in the field of conservative dentistry, but there are still many differences of opinion regarding the ideal amount of time of laser radiation or photoactivation used to reduce the number of bacteria, especially in root canals. Aim. To determine the effective radiation time of the 650 nm wavelength laser diode with Methylene Blue Photosensitizer in reducing the number of bacterial colonies from necrotic root canals. Method. This research is a laboratory experimental study with 30 samples and 6 groups with different durations of irradiation namely 45, 60, 75 and 90 seconds. Results. It was found that there was a decrease in the number of mixed bacterial colonies within necrotic root canals with the obtained p-value of the ANOVA test results being <0.05. This shows that there is a significant difference between the amounts of mixed bacterial colonies from necrotic root canals in each treatment group. Conclusion. Diode laser radiation with a wavelength of 650 nm with duration of 90 seconds of radiation and Methylene Blue Photosensitizer is an effective time in reducing the number of bacterial colonies from necrotic teeth compared to the duration of radiation of 45, 60 and 75 seconds.